Influence of physical qualities on the efficiency of competitive activity of freestyle wrestlers - Kuvanov, V. A.; Mikhailovsky, S. P.; Agaev, R. A.; Davydov, M. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to establish the dependence of the success of competitive activity on the level of development of the physical qualities of student freestyle wrestlers.